The Correlation of Anxiety and Motivation and Speaking Performance of English Foreign Learners - M Arif (Language-Edu, 2020)
AbstractThe primary intention of this paper is to find out the correlation of anxiety and motivation and speaking performance. The respondents were 78 students of English Department in Universitas Islam Madura. The data was composed using a questionnaire (adapted from Horwitz for FLCA Scale, and Gardner for AMTB Survey) and test score was took from the English teacher. The data were analysed using SPSS software to find out the correlation of anxiety and motivation and speaking performance of English Foreign Learners. This study is using a quantitative approach with a research design called multiple Regression, correlating anxiety and motivation simultaneously toward speaking performance, researcher also correlates anxiety and motivation one by one toward the speaking performance to know the stronger predictor. The finding of this study indicated that anxiety and motivations at significantly correlate towards speaking performance. And the writer state out of the two predictors, anxiety was found to be the better predictor of speaking performance.Keywords: anxiety, motivation, speaking performance